(untitled) (The Harvest, 2026)
The Gen Z revolution in Nepal marks a pivotal phase of youth-led public engagement shaped by online interconnectedness, generational consciousness, and broad-based dissatisfaction with political governance. Drawing on multiple theoretical frameworks, this paper explores how Nepal’s Generation Z emerging as digital natives within a context of economic precarity, bureaucratic inertia, and decline in moral standards has transformed individual frustration into collective political action. Methodologically, the study employs qualitative analysis of protest narratives, media discourse, digital platforms, public statements, and secondary literature to explore the motivations, strategies, and symbolic dimensions of the Gen Z uprising. Findings suggest that online tools functioned not merely as means of interaction but as infrastructures of mobilization, enabling decentralized organization, emotional resonance, and rapid diffusion of protest narratives. Social media platforms facilitated the formation of emotionally engaged communities, enabling youth to articulate grievances related to corruption, nepotism, unemployment, and governance failure beyond conventional political avenues. The study further argues that the Gen Z revolution reflects a broader crisis of political legitimacy, as youth challenge deep-rooted hierarchies and reject hierarchical authority in favor of transparency, meritocracy, and ethical leadership. However, the movement also reveals limitations, including organizational fragility, elite co-optation, and the gradual dilution of revolutionary momentum. From a politico-sociological perspective, these dynamics illustrate how institutional power can absorb youth dissent through token gestures without meaningful change. Integrating classical texts, modern political theory, and contemporary digital activism scholarship, this research contributes to understanding how generational identity, digital media, and socio-political structures interact in shaping youthled movements. The paper concludes that The Gen Z cohort in Nepal revolution, despite its challenges, signals a transformative shift in civic consciousness and political participation, offering critical insights into the possibilities and constraints of digital-era governance reform in developing democracies.